Phosphorus availability from olivine for biospheres - Abbatiello, Josh; Henson, John E.; Pasek, Matthew (Frontiers in Astronomy and Space Sciences, 2024)
Phosphorus plays a multifaceted role for all known life and hence understanding its sources on the early Earth provides constraints on how life developed to incorporate this element into its biochemistry. Currently, the major phosphorus mineral group on the surface of the Earth are the apatites, which are poorly soluble calcium phosphates and hence may not have been a good source of phosphorus on the early Earth. An alternative source of phosphorus may be the mineral olivine. Given that olivine makes up a large part of the upper mantle of Earth and presumably other rocky planets and moons, it stands to reason that olivine may be a potential phosphorus reservoir for prebiotic chemical environments. Here we examine the phosphorus content of 10 olivine samples from different terrestrial localities to determine their P content and P speciation. We find that extracts of the samples contain varying amounts of phosphate, and some contain pyrophosphate. Olivine may have served as a source of phosphate on the early Earth and possibly elsewhere in the solar system, and its dissolution could have supplied this nutrient to a nascent biosphere.